Absence of ataxin-3 leads to enhanced stress response in C. elegans. - Ana João Rodrigues; Andreia Neves-Carvalho; Andreia Teixeira-Castro; Anne Rokka; Garry Corthals; Elsa Logarinho; Patrícia Maciel (PLoS ONE, 2011)
Ataxin-3, the protein involved in Machado-Joseph disease, is able to bind ubiquitylated substrates and act as a deubiquitylating enzyme in vitro, and it has been involved in the modulation of protein degradation by the ubiquitin-proteasome pathway. C. elegans and mouse ataxin-3 knockout models are viable and without any obvious phenotype in a basal condition however their phenotype in stress situations has never been described.Considering the role of ataxin-3 in the protein degradation pathway, we analyzed the effects of heat shock, a known protein homeostasis stressor, in C. elegans ataxin-3 (ATX-3) knockout animals. We found that ATX-3 mutants have an exacerbated stress response and survive significantly better than wild type animals when subjected to a noxious heat shock stimulus. This increased thermotolerance of mutants was further enhanced by pre-exposure to a mild heat shock. At a molecular level, ATX-3 mutants have a distinct transcriptomic and proteomic profile with several molecular chaperones abnormally up-regulated during heat shock and recovery, consistent with the observed resistance phenotype.The improved thermotolerance in ATX-3 mutants is independent of heat shock factor 1, the maestro of the heat shock response, but fully dependent on DAF-16, a critical stress responsive transcription factor involved in longevity and stress resistance. We also show that the increased thermotolerance of ATX-3 mutants is mainly due to HSP-16.2, C12C8.1 and F44E5.5 given that the knockdown of these heat shock proteins using RNA interference causes the phenotype to revert. This report suggests that the absence of ATX-3 activates the DAF-16 pathway leading to an overexpression of molecular chaperones, which yields knockout animals with an improved capacity for dealing with deleterious stimuli.